Pelatihan Pembuatan Poster Menggunakan Platform Canva bagi Guru SD - Wahidasiana, Umi; Pramana, Doni Indra; Ardhia, Nur Royce; Nugraha, Fajar (Muria Jurnal Layanan Masyarakat, 2024)
Training activities using the Canva for Education platform for elementary school teachers aim to provide an understanding of making digital posters. Based on this training, nine teaching staff from SD N Banyuurip 02 participated and succeeded in making posters by engaging various features offered. The methods used in this activity are discussion and documentation. The results of the training showed that the teachers were able to make good use of Canva for Education, along with their enthusiasm for understanding Canva's features and how to create learning materials. In general, Canva-based graphic design training activities ran very well and as expected, strengthening the conclusion that teachers can engage this platform to increase creativity in making learning materials.